Penerapan E-Perda Pada Biro Hukum Sekretariat Daerah Provinsi Papua Selatan - Rulof Fabian Yohanis Waas; Fransiskus Samderubun (Universitas Musamus, 2026)
Such recognition and protection are essential to provide legal certainty to the community so that their land rights are not violated by anyone. This state's right to control/control must be strictly limited for the future and it is time to consider alternatives to the state's right to control so that this right can be limited in its conception and implementation. In addition, land management is needed as one of the government's efforts to realize the arrangement of land utilization and use so that the social function of land rights is realized. In the social function of land rights, it does not mean that the interests of individuals or indigenous communities are completely pressured by the public interest. This study uses the Sociolegal method. The results of the study show that customary rights are recognized by the UUPA, but this recognition is accompanied by two conditions, namely regarding